Influence of Fertilizers on Growth and Biomass in Eclipta Alba - an Important Medicinal Plant of Indian Arid Region - Kedia, Sushama; Kasera, Pawan K.; Mohammed, Sher (Indian Forester, 2014)
This article deals with effect of various inorganic and organic fertilizers on growth performance and biomass yield of Eclipta alba, an important medicinal plant of the Indian Thar desert. Results revealed that compost + NPK+ VAM combinations were most favourable to obtain maximum growth and biomass, while minimum in NPK treated plants over control.